Will history repeat itself? Lessons for the yuan - Benjamin J. Cohen (Asian Development Bank Institute (ADBI), 2014)
For many observers, internationalization is the yuan's manifest destiny - an irresistible by-product of the remarkable economic success of the People's Republic of China (PRC). But is such confidence warranted? Recent history has seen the emergence of other currencies that were also expected, at least for a while, to attain wide, growing cross-border use. These included the deutsche mark (DM), the Japanese yen, and the euro (successor to the DM). Yet in the end their internationalization reached an upper limit, short of expectations. Will history repeat itself? Or will the yuan prove exceptional, the currency that finally managed to keep ascending where others faltered? The aim of this paper is to see what lessons may be drawn from these earlier experiences for the anticipated internationalization of the yuan. Much can be learned from their stories - first, about what may drive the internationalization of a currency, and second, about what may ultimately set a limit to the process. The main message of the analysis is that the challenge of internationalization is formidable, involving demanding conditions. Can Beijing sustain its record of price stability and effective policy management? Can the country succeed in shifting its industrial and trade structure toward exports of more advanced differentiated products? Can the yuan's convertibility be broadened? Can domestic financial markets be adequately developed? Can the country's political institutions be trusted? Can geopolitical tensions be avoided? Contrary to predictions of the yuan's "inevitable" rise, success in all these respects is by no means guaranteed.
Keywords: F31; F33; F41; 330; yuan; deutsche mark; japanese yen; euro; internationalization; Wechselkurspolitik; Wirtschaftspolitik; Renminbi; China